Plaza Asia Peduli Mata Bekerjasama Dengan Fakultas Kedokteran Militer Universitas Pertahanan Ri, Rspad, Perdokmil, Dan Oona Insurance - Ibrizatun, Amin; Widuri, Lila Irawati Tjahjo; Wibowo, Markus; Yochanan, E.; Wijayati, Azmi; Ishmatika, Enka Nur; Pannyiwi, Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Visual acuity is a measure of the eye's ability to distinguish the shape and details of an object at a certain distance. To measure visual acuity, you can use the Snellen chart. A refraction examination is an examination that determines the type and magnitude of refractive errors (myopia, hypermetropia and astigmatism). This examination can also provide information on the lens strength needed to correct it. Examination using a slit-lamp can examine the anterior and posterior segments of the eye, which include the conjunctiva, cornea, anterior chamber, pupil, lens and retrolental space. Objective: to carry out early detection of visual impairment by eye examination. The method used is a visual acuity examination with a Snellen chart carried out by an eye specialist, followed by an examination with a slit lamp and a free consultation with an eye specialist. Results: This activity was attended by 120 participants with the results of the examination, most of the participants had myopia, presbyopia, dry eyes and asthenopia. The conclusion is that in this activity there are many cases of myopia, asthenopia and dry eyes, so it is necessary to provide education regarding healthy behavior in using computers, laptops and gadgets by paying attention to distance, lighting, sitting position and the need to do eye exercises.